Factors Affecting Dividend Payout Ratio in LQ-45 (Non-Banking) Companies Listed in Indonesia Stock Exchange, 2011-2019 - Cindy Claudia Pandoyo; Gracia Shinta Setyadi Ugut (Enrichment : Journal of Management, 2021)
Dividend policy determines the placement of profits, among others, to be paid to shareholders and reinvested by the company. The purpose of this study was conducted to assess the factors that affect the Dividend Payout Ratio (DPR) in non-banking companies listed on the LQ-45 Index by using the variables which are age of company, tangible assets, leverage, firm size, profitability, and dividend of previous period. This research is a quantitative study using secondary data taken from audited company financial reports and included in the LQ-45 index on the Indonesia Stock Exchange (BEI) 2011-2019 with the criteria of companies that are consistent in paying dividends and published audited financial reports for the years 2011-2019. The research sample used purposive sampling method with data analysis method in the form of panel data regression analysis, then the best model was tested and the classical assumption test. The results of the study indicate that age of company has a significant positive effect on the dividend payout ratio (DPR). Meanwhile, firm size, profitability and dividend of previous period have a significant negative effect on dividend payout ratio (DPR), and tangible assets and leverage have no effect on dividend payout ratio.